FRIDAS GRYDE: Moral, modernitet og mad i det vestlige Kenya - Teglhus, Lene (Tidsskriftet Antropologi, 2004)
Frida is a young widow who resists the tradition of levirate, that stipulates that a widow should marry one of her dead husmands brothers or a professional levir. This opposition results in her exclusion from family. Therefore she can expect no help or food from her mother-in-law. She suffers from disease and from uncertainty, and every day of her life is a struggle for survival for herself and her two children. To understand the stakes and concerns involved in this struggle, the article draws upon classical analysis of kinship as well as more recent analytic approaches to relatedness. By negotiating rights and morality, Frida deals with aspects of modernity and tradition in coping with situations where there are questions of her inclusion and exclusion..